Two interpenetrated metal–organic frameworks with a slim ethynyl-based ligand: designed for selective gas adsorption and structural tuning. Issue 39 (4th July 2018) - Kong, Xiang-Jing; Zhang, Yong-Zheng; He, Tao; Wu, Xue-Qian; Xu, Ming-Ming; Wang, Si-Nan; Xie, Lin-Hua; Li, Jian-Rong
Abstract : Structural tuning and selective gas adsorption of two interpenetrated metal–organic frameworks using a slim ethynyl-based ligand were achieved. Abstract : In the design and construction of metal–organic frameworks (MOFs), the utilization of slim ligands is usually more inclined to form interpenetrated structures compared with bulky ones. The structural interpenetration can improve the framework stability and in some cases, enhance gas adsorption capacity and selectivity due to confined pores. In order to explore the structural control of MOFs and construct new MOFs with good selective gas adsorption ability, herein, a slim ethynyl-based 4-connected carboxylate acid ligand, 4, 4′, 4′′, 4′′′-(benzene-1, 2, 4, 5-tetrayltetrakis(ethyne-2, 1-diyl))tetrabenzoic acid (H4 BTEB), was used to design and construct MOFs, hopefully having interpenetrated structures. Combining with 4-connected paddle-wheel Cu2 (COO)4 and 8-connected Zr6 O4 (OH)8 (COO)8 clusters, BTEB 4− ligand led to two new MOFs, [Cu2 (BTEB)(H2 O)2 ] (BUT-43) and [Zr6 O4 (OH)8 (H2 O)4 (BTEB)2 ] (BUT-44). As expected, the two MOFs have two-fold interpenetrated framework structures with partitioned channels. BUT-43 contains a rare three-dimensional (3D) 4-connected single network with lvt topology, which then interpenetrates. In BUT-44, each Zr6 -based cluster is coordinated with eight BTEB 4− ligands to give a single 3D 4, 8-connected scu network, which then doubly interpenetrates to give the first example of interpenetrated 4, 8-connected Zr(iv )-MOF. Studies on their stability and gas adsorption properties demonstrate that BUT-44 shows higher stability in NaOH solution of pH 10 and 1 M HCl aqueous solution. More interestingly, both MOFs represent good gas adsorption selectivities for C2 H2 over CO2 and CH4, suggesting potential application in gas separation.